Enabling High‐Rate and Safe Lithium Ion–Sulfur Batteries by Effective Combination of Sulfur‐Copolymer Cathode and Hard‐Carbon Anode. Issue 2 (17th January 2019) - Nguyen, Dan Thien; Hoefling, Alexander; Yee, Minha; Nguyen, Giang Thi Huong; Theato, Patrick; Lee, Young Joo; Song, Seung‐Wan
Abstract: Fabrication and high‐rate performance of a safe lithium ion–sulfur battery (LISB) with sulfur‐copolymer [poly(S‐ co ‐divinylbenzene (DVB)] cathode having a sulfur content higher than 90 wt %, a carbon‐fiber interlayer, and a prelithiated hard‐carbon (Li‐HC) anode are reported, which mitigates problems of lithium–sulfur cells such as performance fade and safety issues due to dissolution of polysulfides and lithium‐dendrite growth. The poly(S‐ co ‐DVB) cathode offers scalability owing to the abundance and low cost of DVB. The Li‐HC anode, the surface of which is passivated by a solid electrolyte interphase, inhibits the deposition of polysulfides. As a result, the LISB exhibits reversible and stable cycling performance at high rates up to 3 C, which enables quick charging within 20 min, and delivers a reversible capacity of approximately 400 mAh g −1 at 3 C for 500 cycles. The results give insight into the design principle of promising, quickly charged, and safe LISBs. Abstract : Faster and safer : Safe and stable Li ion–S batteries with sulfur–divinylbenzene (S‐DVB) copolymer cathode, carbon‐fiber (CF) interlayer, and prelithiated hard‐carbon anode exhibit stable high‐rate cycling performance up to 3 C by mitigating problems of Li–S cells such as performance fade and safety issues due to dissolution of polysulfides and lithium‐dendrite growth.